Organizational and Economic Aspects of the Development of the International Tourism and Hospitality Industry - SAFAEVA, Sayyora Rikhsibaevna; ALIEVA, Maxbuba Toychievna; ABDUKHALILOVA, Laylo Toktasinovna; ALIMKHODJAEVA, Nargiza Elshodovna; KONOVALOVA, Elena Evgenievna (Journal of Environmental Management and Tourism, 2020)
The article is devoted to the consideration of aspects related to the development of the tourism and hospitality industry in Uzbekistan and Russia. It has been established that the intensive development of various forms of tourism and hospitality will allow these countries to be more attractive for foreign tourists. It has been found that when developing the tourism and hospitality market Uzbekistan and Russia are advised to review prospects of its development at the international level. Promising areas of the development in the tourism and hospitality industry will be a new system of enterprise classification regulating the rating of enterprises and encouraging tourism by simplifying visa regulations, applying discounts to attract regular and potential tourists, introducing educational programs in the tourism and hospitality sector combining theory and practice, and spurring the development of all regions as potential tourist destinations.